2017
DOI: 10.3390/md15060181
|View full text |Cite
|
Sign up to set email alerts
|

How Environmental Factors Affect the Production of Guanidine Alkaloids by the Mediterranean Sponge Crambe crambe

Abstract: Most marine sponges are known to produce a large array of low molecular-weight metabolites which have applications in the pharmaceutical industry. The production of so-called specialized metabolites may be closely related to environmental factors. In this context, assessing the contribution of factors like temperature, nutrients or light to the metabolomes of sponges provides relevant insights into their chemical ecology as well as the supply issue of natural sponge products. The sponge Crambe crambe was chose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 64 publications
1
18
0
Order By: Relevance
“…Conversely, seasonal effects were apparent. 521 An independent detailed investigation of the absolute conguration of aurantosides G and J using computational approaches has validated the results suggested by total synthesis. 522 A metagenomic analysis of the microbial community associated with the chemically prolic sponge Theonella swinhoei has identied a new pathway to the keramamides, sponge-derived peptides containing the rare halohydroxytryptophan motif.…”
Section: Spongesmentioning
confidence: 57%
“…Conversely, seasonal effects were apparent. 521 An independent detailed investigation of the absolute conguration of aurantosides G and J using computational approaches has validated the results suggested by total synthesis. 522 A metagenomic analysis of the microbial community associated with the chemically prolic sponge Theonella swinhoei has identied a new pathway to the keramamides, sponge-derived peptides containing the rare halohydroxytryptophan motif.…”
Section: Spongesmentioning
confidence: 57%
“…There is still a debate whether changing environmental conditions such as temperature produces variations in the production of specialized metabolites. Several studies have found higher concentrations of specialized metabolites in summer corresponding to maximum yearly temperatures (Abdo et al 2007;Ternon et al 2017;De Caralt et al 2013) while other studies failed to find seasonal changes in production of metabolites (Duckworth et al 2012;López-Legentil et al 2006). In this study, a clear decrease of specialized metabolites occurred in April and May, when temperature in the Northwestern Mediterranean starts to increase after winter (http://somlit.mio.univ-amu.fr), but no further variation occurred during the warmest period (August-October), indicating the fluctuation in the metabolomes might be due to sponge physiological responses rather than environmental parameters.…”
Section: Discussionmentioning
confidence: 99%
“…In the marine environment, spatial and temporal variations of specialized metabolites have been studied in algae (Payo et al 2011;Soares et al 2015), cnidarians (Kelman et al 2000;He et al 2014;Costa-Lotufo et al 2018), tunicates (López-Legentil et al 2006), bryozoans (Peters et al 2004) and sponges (Reverter et al 2016;Ternon et al 2017;Sacristan-Soriano et al 2011). Spatial variation of metabolites has been mostly related to local adaptation to the environment and fluctuating parameters such as temperature, light, or chlorophyll concentrations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An example of a study of a sponge species which did not differ in metabolite concentration is that of the sponge Crambe crambe which was collected from different geographical regions in the Mediterranean (Liguarian Sea and Sardinia Sea) and examined for the occurrence of crambescidins and crambescins [21].…”
Section: Introductionmentioning
confidence: 99%